Resistance is mobile: Dynamics of repression, challenger adaptation, and surveillance in US 'Red Squad' and black nationalist archives. (March 2018) - Sullivan, Christopher M; Davenport, Christian
An emerging consensus holds that achieving successful counter-movement outcomes requires combining overt repression (e.g. raids, arrests, and targeted assassination) with covert repression (e.g. monitoring, agents provocateurs, and wiretapping). Research in this article disputes the presumed complementarity between overt and covert repressive tactics. When overt repression signals new information about the state's covert intelligence collection program, challengers respond in ways that frustrate efforts to accumulate new intelligence. These propositions are investigated using original, weekly panel data on a black nationalist insurgent organization, the Republic of New Africa (RNA), and US Red Squad counter-movement activities directed against this group (between 1968 and 1971). Using archived materials generated by various policing agencies and their rivals in the RNA, the analyses provide new understanding of dynamics rarely observed or analyzed systematically. Findings reveal that the two methods of political repression can work at cross purposes. Overt repression motivates challenger adaption towards less readily observable tactics and organizational forms; covert repression subsequently fails to identify challengers' actions or identities. These findings hold even while controlling for challenger mobilization and government investment in covert repression. In addition to advancing our understanding of what happens to behavioral challengers when governments repress, the results help to shed light on some of the factors that make defeating domestic challengers so difficult. Each 'step forward' taken by counter-movement forces potentially makes the next one more difficult.